A Mobile based Tuberculosis contact tracing and screening system - Mwongela, Stanslaus Wambua (Strathmore University, 2018)
The National TB programme in Kenya is facing some significant challenges as relates to TB contact tracing and screening. Tuberculosis contact tracing and screening is typically conducted in resource-limited settings with paper forms. This approach presents a number of challenges, first is the challenge of covering vast geographical locations with the limited number of health workers. The approach is also limited by inefficiencies in data collection, storage, retrieval and poor data quality. These limitations of the current contact tracing and screening, have made the National TB Programme in Kenya fall short of reaching its objectives in combating TB and consequently the country has experienced an increase in TB rates. This scenario creates a significant gap, which the researcher can help close by improving the current way of TB contact tracing and screening. This study aimed to come up with a mobile-based system for TB contact tracing and screening using USSD technology and Android technology. Agile methodology was adopted as the software methodology for developing the system. An Android application was developed for the use of identifying TB contacts, alerting TB contacts to screen their symptoms and risk factors and recording laboratory results of TB contacts. Further, a USSD application was developed to allow TB contacts to select their symptoms, risk factors and to check status of their screening results. Both the USSD application and Android application were integrated with analytical back-end for presenting summary of the activities of contact tracing and screening. The TB contact tracing and screening system was developed and designed to benefit from the high mobile phone availability and usage in Kenya, to improve TB contact tracing and screening and tackle the inefficiencies of surveillance based on paper records. The system also improves decision making by TB policy officials by providing them with relevant surveillance reports, analytics and statistics.
A Dissertation submitted in partial fulfillment of the requirements for the Degree of Master of Science in Mobile Telecommunications and Innovation (MSc. MTI)
Keywords: TB contact tracing; TB contact screening; TB mobile applications